Analisis Yuridis Konsolidasi Tanah Pedesaan Atas Tanah Ulayat Masyarakat Hukum Adat - Manik, Regen; Idham, Idham (ARBITER: Jurnal Ilmiah Magister Hukum, 2021)
The implementation of rural land consolidation is carried out in accordance with the existing stages, as well as with the existing implementation instructions. The implementation of land consolidation has benefits for landowners affected by consolidation, among others: land becomes organized in terms of shape, area and location, increased benefits and value of land, the environment is well organized, does not incur costs, and the availability of public facilities for the common good. The benefits received by the government include: making it easier for the government to carry out development projects according to the spatial plan, creating areas in accordance with the principles of environmental management, which means there is legal certainty for development in accordance with the designation of the land or area. Another benefit is that it really helps the land certification process as an orderly land administration and the location of the object of consolidation can be made a map. The obstacles that occur in the implementation of land consolidation are the land area is not in accordance with the attached SPPT (Tax Notice Payable), then the settlement of these obstacles the consolidation implementation committee re-measures the parcel of land.